Analisis Jaringan Petri pada Jalur Angkutan Umum di Jombang Menggunakan Aljabar Max-Plus - Rakhmawati, Nahlia; Hartiningrum, Esty Saraswati Nur (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2018)
The aim of this research is to get a representation of public transport systems in max-plus algebra after the system is simulated into the timeless petri net function. The analysis includes how to simulate the model of public transport transportation on the petri net function and then convert it into the form of a max-plus algebra matrix and then compile a model that meets